ORTHOPEDIC INJURIES IN ADOLESCENT GYMNASTS: A SYSTEMATIC REVIEW. Issue 7 (30th July 2021) - Kim, Katie; Saper, Michael
Background: Gymnastics exposes the body to many different types of stressors ranging from repetitive motion, high impact loading, extreme weight bearing, and hyperextension. These stressors predispose the spine and upper and lower extremities to injury. In fact, among female sports, gymnastics has the highest rate of injury each year. Purpose: The purpose of this study was to systematically review the literature on location and types of orthopedic injuries in adolescent (≤20 years) gymnasts. Methods: The Pubmed, Medline, EMBASE, EBSCO (CINAHL) and Web of Science databases were systematically searched according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines to identify all studies reporting orthopedic injuries in adolescent and young adult gymnasts. All aspects of injuries were extracted and analyzed including location, type and rates of orthopedic injuries. Results: Screening yielded 22 eligible studies with a total of 427, 225 patients. Twenty of 22 studies reported upper extremity injuries of which four specifically focused on wrist injuries. Eight studies reported lower extremity injuries. Nine studies reported back/spinal injuries. Seven studies investigated each body location of injury; one study reported the upper extremity as the most common location for injury and six studies reported the lower extremity as the most common location for injury. Of those seven studies, five (23%) reported sprains and strains as the most common injury. One study reported fractures as the most common injury. Conclusion: There is considerable variation in reported injury location. Some studies focused specifically on the spine/back or wrist. The type of gymnastics each patient participated in was also different, contributing to which area of the body was more heavily stressed, or lacking. Current literature lacks data to fully provide evidence regarding which body region is more frequently injured and the type of injury sustained.